1991
DOI: 10.1002/nur.4770140608
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive distortion and depression on disability in rheumatoid arthritis

Abstract: The question explored in this study was: What is the effect of cognitive distortion and depression on disability in arthritis patients when stage of disease is controlled? Patients (N = 165) completed the Sickness Impact Profile, two Cognitive Error Questionnaires, and the Symptom Questionnaire, and were staged for severity of disease. Findings indicated a significant effect of distortion on disability in rheumatoid arthritis patients; however, this effect varied by stage. Distortion and depression best explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…It is also possible that the specific instruction around identifying and re structuring negative cognitions was responsible for the decrease in the level of psychosocial disability. This is consistent with the model proposed by Clough [12] that indicates that distortion has a direct effect on disability.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It is also possible that the specific instruction around identifying and re structuring negative cognitions was responsible for the decrease in the level of psychosocial disability. This is consistent with the model proposed by Clough [12] that indicates that distortion has a direct effect on disability.…”
Section: Discussionsupporting
confidence: 81%
“…Subscores include catastrophizing, overgeneraliza tion, personalization, and selective abstraction [29]. The reliability and validity of the CEQ have been demonstrated for various chronic illness populations [12,29]. The COPD-CEQ was evaluated for face validity by an expert in chronic illness and was piloted with four COPD patients prior to this study.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The other participants chose not to dwell on that aspect of their lives, but instead related the activities that moved them forward beyond painful moments. In quantitative studies researchers have identified an exaggerated appraisal of the environment and cognitive distortions and depression among those with RA (Clough, 1991). While the men and women in this study used the terms sadness and occasionally depressed, unpleasant feelings were not a frequent topic nor were the thoughts and actions reported indicative of depression.…”
Section: Discussionmentioning
confidence: 94%
“…Perception of support needs and of their fulfilment is closely associated with subjects' coping behaviors, and therefore can vary greatly among individuals. [26][27][28] The roles of family care and social support in the management of RA patients remain to be studied. 29 In this study, the validity of the questionnaire was assessed by internal standards, based on the premise that if several questions measure the same or related things, then they should be highly correlated with one another.…”
Section: Reliability Of Satisfaction Attribution and Priority Sectionsmentioning
confidence: 99%